THE LUDICOVIAN-KALEVIAN BOUNDARY IN THE NORTHERN LADOGA REGION: GEOLOGICAL RELATIONS AND ISOTOPIC AGE - Matrenichev V.A.; Vrevsky A.V.; Sergeev S.A.; Matukov D.A. (My University, 2006)
Supracrustal rocks in the northern Ladoga region are mainly represented by rock associations of the Karelian Complex (2.1–1.65 Ga). The section is divided into the Ludicovian Suprahorizon (metavolcanites of the Sortavala Group) and the Kalevian Suprahorizon (metaturbidites of the Ladoga Group) with the boundary at 1920 ± 50 Ma. The regional stratigraphy and the volume of the Karelian Complex in the northern Ladoga region are debatable issues. Relationships between the Kalevian and Ludicovian supracrustal complexes are ambiguously interpreted, but in general it is postulated that the higher stratigraphic position of the Ladoga Group “stems from the general structure of the region”. The upper age limit for Kalevian rocks is determined by the maximal age of intrusions estimated at 1892 ± 5 Ma (based on zircon from monzo-diorites of the Velimyak Pluton). The lower age boundary is based on the minimal age of clastogenic zircons estimated at 1907 ± 15 Ma (metaturbidites of the Tampere Belt).
Keywords: northern Ladoga region; Karelian Complex